Ritual and Sprituality: The Tradition of the Tariqah Naqshabandiyyah Khalidiyyah Jalaliyyah in Indonesia - Rosidi, Imron; Masduki,; Ginda,; Arwan,; Darusman,; Titi Antin,; Miftahuddin, (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
The Sufi Order, known as tariqah, played a significant role during the initial Islamization period in Indonesia, further solidifying the distinct identity of Islam in the country. However, compared to other mainstream Islamic organizations like Nahdlatul Ulama and Muhammadiyah, tariqah has received relatively little study. In light of recent developments in Indonesia, particularly the conservative turn in Indonesian Islam, there is an increased significance in studying tariqah. This is because it provides insights into the diversity within Indonesian Islam, highlighting that the phenomenon of the conservative turn is not monolithic. Through observation and interviews, this article explores the rituals of the tariqah Naqshabandiyyah Khalidiyyah Jalaliyyah, which are routinely conducted based on Sufi spiritual concepts such as purification, admission, and illumination. These phases aim to enhance the spirituality of tariqah members through moral purification. This underscores that the essence of the ritual is to gradually and cumulatively improve the spiritual quality of its members. The transformation from one phase to another reflects the caliber of its members, ultimately leading to the attainment of the perfect man, a concept describing spiritual perfection for both worldly life and the hereafter.